Influence of shear stress on the structures and properties of polyamide 6/montmorillonite nanocomposites - Mencel, K.; Kelar, K.; Jurkowski, B. (Polimery, 2022)
The effects of shear stress occurring during polyamide 6/montmorillonite nanocomposites’ extrusion, with use of static and dynamic prototype mixers, on the dispersion degree of organically modified montmorillonite (OMMT) in polyamide matrix (PA 6) and on the structure as well as thermal and mechanical properties of PA 6/MMT were presented. MMT dispersion degree was analyzed based on SEM micrographs of fractures’ surfaces and mapping of silicon atoms distributions in nanocomposites. It was found that MMT dispersion in polymer matrix clearly depends on shear stress (Fig. 1) and that MMT presence influences the process of PA 6 crystallization in nanocomposite (Fig. 2, Table 2). In spite of not quite homogeneous dispersion of MMT in a matrix, tensile modulus and strength (Table 4) as well as thermal stability (Fig. 4, Table 2) of nanocomposites are better than for unmodified PA 6. Nanoparticles of clay in nanocomposites favor the formation of more ductile crystallographic ?-form (Fig. 3, Table 2). Better values of strength and tensile modulus of nanocomposites show that not the crystallographic form but MMT dominantly influences these features. Excessive shear stress causes partial degradation of macromolecules (Table 1). The results showed that elongation at break and notched impact strength of nanocomposites were lower than those of unmodified PA 6.